We can solve the equation by isolating the variable x.
First, let's clear the fractions by multiplying both sides of the equation by the least common denominator which is 6.
(6)(5/3 - 2x) = (6)(1/6)
After multiplying both sides, we get:
(6)(5/3) - (6)(2x) = 1
Now, simplify each term:
10 - 12x = 1
Next, we can isolate the variable x by subtracting 10 from both sides of the equation:
10 - 12x - 10 = 1 - 10
This simplifies to:
-12x = -9
Finally, divide both sides of the equation by -12 to solve for x:
-12x / -12 = -9 / -12
x = 9/12
Simplifying the fraction, we get:
x = 3/4
Therefore, the solution to the equation 5/3 - 2x = 1/6 is x = 3/4.
What is the solution of the equation 5/3−2x=1/6?(1 point)
1 answer